1998
DOI: 10.1007/bf02464784
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neurotransmitters in multiple sclerosis

Abstract: Patients with multiple sclerosis were found to have increased cerebrospinal fluid, noradrenaline, and excitatory amino acid (glutamate and aspartate) levels, with increased blood glutamine, asparagine, and glycine levels. An association was found between these biochemical parameters and the nature and severity of neurological symptoms, as well as with the course of the disease. Neurotransmitters are proposed to have a role in the pathogenesis of multiple sclerosis, particularly in the biochemical mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…It is widely accepted that the most common pathological abnormality in MS is an inflammatory demyelination in the CNS, but recent studies have highlighted the additional presence of axonal damage (37,38). The cause of demyelination and axonal damage remains unclear, but several lines of evidence support the possibility that glutamate-induced excitotoxicity plays a role in these pathological changes in MS. Glutamate concentration in the cerebrospinal fluid (CSF) is reported to be elevated in patients suffering from acute MS (39,40). In EAE, glutamate-metabolizing enzymes, glutamine synthetase, and glutamate dehydrogenase are downwardly regulated in astrocytes (41).…”
mentioning
confidence: 99%
“…It is widely accepted that the most common pathological abnormality in MS is an inflammatory demyelination in the CNS, but recent studies have highlighted the additional presence of axonal damage (37,38). The cause of demyelination and axonal damage remains unclear, but several lines of evidence support the possibility that glutamate-induced excitotoxicity plays a role in these pathological changes in MS. Glutamate concentration in the cerebrospinal fluid (CSF) is reported to be elevated in patients suffering from acute MS (39,40). In EAE, glutamate-metabolizing enzymes, glutamine synthetase, and glutamate dehydrogenase are downwardly regulated in astrocytes (41).…”
mentioning
confidence: 99%
“…Increased levels of glutamate were observed in the cerebrospinal fluid from MS patients, 6 and a correlation was shown between the cerebrospinal fluid glutamate and the disease activity and severity. 7 CNS-infiltrating macrophages and activated microglia are probably the major sources because these cells release large quantities of glutamate after activation in vitro. 8,9 Moreover, both glutamate degradation enzymes and glutamate transporters were markedly reduced in MS and EAE lesions.…”
mentioning
confidence: 99%
“…This hypothesis is based upon various lines of evidence. Thus, glutamate levels are elevated in cerebrospinal fluid in acute episodes of MS (Stover et al, 1997) and have been found to be associated with the severity of the disease (Barkhatova et al, 1998). The impairment of glutamate uptake reported in MS lesions (Werner et al, 2001) may contribute to these alterations.…”
mentioning
confidence: 99%